Реакция двух цветных форм (черной и рыжей) хомяка обыкновенного (Cricetus cricetus L.) на градиент температуры - Самош, В.М. (Вестник зоологии, 1969)
Experiments carried out in the Herter’s chamber showed the elective ability of the black and red hamsters with respect to substrate temperature. The black hamsters, inhabitants of the moistened habitats, preferred the lower temperatures than the red ones, the representatives of dry biotopes.
A supposition is made that differences in reaction of black and red hamsters on gradient of temperature, probably, reflect those microclimatic where adaptation of the species occurred to the definite landscape-climatic zones in the process of evolution